Cardiac obstetric care in Botswana - Mwita, Julius Chacha; Goepamang, Monkgogi; Sliwa, Karen (SA Heart Journal, 2022)
Cardiovascular diseases (CVD) in pregnancy are significant causes of maternal mortality in Botswana. Like other developing countries, acquired CVD such as hypertensive disorders, rheumatic heart disease and cardiomyopathy are common in Botswana. CVD-related maternal deaths are often attributed to failure to provide risk-appropriate care. A multidisciplinary pregnancy heart team is an essential approach in managing CVD in pregnancy and improving maternal and foetal outcomes. Given that more women with CVD are becoming pregnant in Botswana, we review the current practice, gaps, and potential areas of improvement.